Australian motor sport enthusiasts’ leisure information behaviour - Joseph, Pauline (2016)
Purpose: This paper explores the leisure information behaviour of motor sport enthusiasts, examining: their information needs; their information seeking and sharing; what personal information they had; and their satisfaction with their information seeking and personal information management efforts. Method: This exploratory study examined participants’ information behaviour from a postpositivist and inductive research approach. An online survey was completed by 81 motor sport enthusiasts. Analysis: The quantitative survey data were analysed using descriptive statistics, whilst the qualitative data were analysed using thematic coding. Findings: The research findings highlighted that enthusiasts engaged in mixed serious leisure. They required information before, during, and after race events, and sought this primarily from online sources, as well as from other individuals. Ninety participants shared information about their interest in motor sport with family, friends, and fellow enthusiasts, primarily via emails (69%) and Facebook (49%). They also gathered information about motor sport, including photographs and memorabilia. Participants were satisfied with their information management strategies for their personal collections. Limitations: Participants were limited to motor sport enthusiasts in Australia, hence findings cannot be generalised more broadly. Originality/Value: This study fills a gap in the literature about leisure information behaviour of motor sport enthusiasts in Australia. It identifies and provides a typology of the 12 categories of information needed by enthusiasts. Further, introduces a preliminary Motor Sport Information Behaviour Model. These understandings of enthusiasts’ information behaviour provide information management professionals with insights to work with this user community.